У пошуках витокiв слов’ян. До 100-рiччя вiд дня народження Є. В. Максимова - Абашина, Н.С. (Археологія, 2021)
У статті розглядається життєвий шлях і наукова
спадщина відомого українського археолога, дослідника
проблем походження слов’ян і давньої історії України Євгена Володимировича Максимова. Провідне місце у його
науковому доробку посідають дослідження зарубинецької
культури — проблема формування культури, її хронологія, історична доля. 28 января 2021 г. исполнилось 100 лет со дня рождения известного украинского археолога, исследователя проблем
происхождения славян, доктора исторических наук, профессора, лауреата Государственной премии Украины в
области науки и техники (1991) Евгения Владимировича Максимова.
В 1949 г. Е. В. Максимов окончил Киевский университет имени Т. Г. Шевченко. С 1949 по 1998 гг. он работал в
Институте археологии НАН Украины, в отделе археологии ранних славян — со дня его создания в 1974 г. В 1968 г.
Е. В. Максимов защитил кандидатскую диссертацию, в 1983 г. — докторскую диссертацию.
Е. В. Максимов исследовал археологические культуры лесостепной территории Украины I тыс. до н. э. —
I тыс. н. э. Он провел раскопки и ввел в научный оборот материалы памятников зарубинецкой культуры — городищ Пилипенкова Гора, Бабина Гора, Монастырек, могильников Пирогов, Козаровичи, Дедов Шпиль и др.
В научном наследии Е. В. Максимова более 200 печатных работ. Ведущее место занимают исследования,
связанные с зарубинецкой культурой: проблема формирования культуры, ее хронология, анализ основных категорий материала и их изменений во времени под действием внутренних и внешних факторов.
Е. В. Максимов первым среди исследователей доказал, что зарубинецкая культура не является модификацией
какой-либо одной культуры — местной или перенесенной мигрантами из Центральной Европы. Зарубинецкая
культура — новообразование. Она возникла в результате интеграции культурных традиций мигрантов и местного населения. От мигрантов в зарубинецкой культуре появились элементы латенской культуры. Е. В. Максимов
впервые использовал фрагменты античных амфор из зарубинецких памятников Среднего Поднепровья как хронологические реперы и определил, что ранней датой культуры является конец III в. до н. э. или рубеж III/II вв.
до н. э.
Памятники позднего периода позволили Е. В. Максимову понять историческую судьбу зарубинецкой
культуры. Они стали основой киевской культуры, которая демонстрирует генетическую близость к культурам
славян VI—VII вв. Е. В. Максимов предполагал, что носители зарубинецкой культуры близки к праславянам и
считал, что в этногенезе славян зарубинецкая культура сыграла значительную роль. On January 28, 2021 there was the 100th anniversary of the birth of, Yevhen Volodymyrovych Maksymov, the famous
Ukrainian archaeologist, researcher of the problems of the Slavs’ origin, Doctor of Historical Sciences, professor, laureate
of the State Prize of Ukraine in the field of science and technology (1991).
In 1949 Ye. V. Maksymov graduated from the Taras Shevchenko National University of Kyiv. From 1949 to 1998 he
worked at the Institute of Archaeology of the National Academy of Sciences of Ukraine, in the Department of Early Slavic
Archaeology from the day of its creation in 1974. In 1968 he defended his Ph.D. thesis, in 1983 he defended his doctoral
dissertation.
Ye. V. Maksymov studied archaeological cultures of the Ukrainian Forest-Steppe in the 1st millennium BC — 1st
millennium AD. He conducted excavations and introduced into scientific circulation the materials of Zarubyntsi culture
sites: the settlements of Pylypenkova Hora, Babyna Hora, Monastyrok, the burial grounds of Pyrohiv, Kozarovychi, Didiv
Shpil and others.
In the scientific heritage of Ye. V. Maksymov there are more than 200 publications. The leading place is occupied
by research related to Zarubyntsi culture — the problem of its formation, chronology, analysis of the main categories of
material and their changes over time under the influence of internal and external factors.
Ye. V. Maksymov was the first among the researchers to prove that the Zarubyntsi culture is not a modification of any
one culture — local or transferred by migrants from Central Europe. Zarubyntsi culture is a new historical formation. It arose
as a result of the migrants’ cultural traditions integration and the local population. From the Zarubyntsi culture migrants
occurred elements of the La Tène culture. Ye. V. Maksymov first used fragments of ancient amphorae from Zarubyntsi sites
of the Middle Dnieper as chronological benchmarks and determined that the early date of the culture is the end of the 3rd
century BC or the boundary of the 3rd /2nd century BC.
Sites of the late period allowed Ye. V. Maksymov to understand the historical fate of the Zarubyntsi culture. They
became the basis of the Kyiv culture, which demonstrates the genetic relationship to the cultures of the Slavs of the 6th—7th
centuries Ye. V. Maksymov suggested that the bearers of the Zarubyntsi culture were close to the Proto-Slavs and believed
that this culture played a significant role in the Slavs’ ethnogenesis.